Spectral emissivity measurements of Mercury's surface indicate Mg- and Ca-rich mineralogy, K-spar, Na-rich plagioclase, rutile, with possible perovskite, and garnet - Sprague, A; Donaldson Hanna, K; Kozlowski, R; Helbert, J; Maturilli, A; Warell, J; Hora, J (Elsevier, 2009)
Mid-infrared 2-D spectroscopic measurements from 8.0 to 12.7 μm of Mercury were taken using Boston University's Mid-Infrared Spectrometer and Imager (MIRSI) mounted on the NASA Infrared Telescope Facility (IRTF) on Mauna Kea, Hawaii, 7–11 April 2006. Measurements reported here cover radar bright region C, a dark plains region west of Caloris Basin, and the interior of Caloris Basin. By use of spectral deconvolution with a large spectral library composed of many mineral compositions and grain size separates, we fitted, or “unmixed”, the Mercury spectra. We find mineral suites composed of magnesium-rich orthopyroxene and olivine, Ca-, Mg-, Na-rich clinopyroxene, potassium feldspar, and Na-bearing plagioclase feldspar. Both Ca- and Mg-rich garnet (pyrope and grossular, respectively) are apparently present in small amounts. Opaque minerals are required for spectral matching, with rutile (TiO2) repeatedly providing the “best fit”. However, in the case of the radar bright region C, perovskite also contributed to a very good fit. Caloris Basin infill is rich in both potassium feldspar and Na-rich plagioclase. There is little or no olivine in the Caloris interior smooth plains. Together with the high alkali content, this indicates that resurfacing magmas were low to intermediate in SiO2. Data suggest the dark plains exterior to Caloris are highly differentiated low-iron basaltic magmas resulting in material that might be classified as oligoclase basalt